2016
DOI: 10.1371/journal.pone.0166336
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus D-68 Infection, Prophylaxis, and Vaccination in a Novel Permissive Animal Model, the Cotton Rat (Sigmodon hispidus)

Abstract: In recent years, there has been a significant increase in detection of Enterovirus D-68 (EV-D68) among patients with severe respiratory infections worldwide. EV-D68 is now recognized as a re-emerging pathogen; however, due to lack of a permissive animal model for EV-D68, a comprehensive understanding of the pathogenesis and immune response against EV-D68 has been hampered. Recently, it was shown that EV-D68 has a strong affinity for α2,6-linked sialic acids (SAs) and we have shown previously that α2,6-linked S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 67 publications
5
39
2
Order By: Relevance
“…Notably, despite having direct access to the nose upon infection, we observed less viral shedding from nasal discharges compared to fecal matter. Instead, the most impressive viral burdens were noted in the lung, which were similar to the experimental results for cotton rats [13]. While the EV-D68 infection was not measured directly by viral titration in our study, the results of qRT-PCR for viral genome and immunohistochemical analysis for viral antigens can support the EV-D68 virus replication in infected ferrets.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Notably, despite having direct access to the nose upon infection, we observed less viral shedding from nasal discharges compared to fecal matter. Instead, the most impressive viral burdens were noted in the lung, which were similar to the experimental results for cotton rats [13]. While the EV-D68 infection was not measured directly by viral titration in our study, the results of qRT-PCR for viral genome and immunohistochemical analysis for viral antigens can support the EV-D68 virus replication in infected ferrets.…”
Section: Discussionsupporting
confidence: 86%
“…The neutralization antibody GMT exhibited a slight and slow increase of 1:16 levels at week 4 after inoculation ( Figure 6). With respect to the report by Patel et al, in the EV-D68 Cotton rat model, Fermon infection resulted in no detectable neutralization antibody (NA) response [13]. Findings in this study demonstrate that the EV-D68 Fermon strain infection may induce faint immunological response in the form of the neutralization antibody titer in ferrets.…”
Section: Immunological Response Of Ferrets After Ev-d68 Infectionsupporting
confidence: 49%
See 2 more Smart Citations
“…While some picornaviruses have been determined to have multiple open reading frames with an additional start codon in the 5' UTR, this is not the case for EV-D68 [61,62]. There has been substantial evolution in the EV-D68 5' UTR since its initial discovery in 1962, most notably in the form of heightened variability and large deletions in the spacer region flanking the AUG start codon [63,64]. Our studies identified a loss of temperature sensitivity in recent EV-D68 strains which was associated with increased translation of the viral genome.…”
Section: Introductionmentioning
confidence: 99%